Between Hollywood and Moscow : the Italian communists and the challenge of mass culture, 1943-1991 - Gundle, Stephen, 1956- (American encounters/global interactions., 2000)
A study of the cultural policies of the Italian communist party following the collapse of fascismand the struggle with popular consumer culture that led to its demise in 1991.